2016
DOI: 10.1111/gcb.13333
|View full text |Cite
|
Sign up to set email alerts
|

Multiyear dual nitrate isotope signatures suggest that N‐saturated subtropical forested catchments can act as robust N sinks

Abstract: In forests of the humid subtropics of China, chronically elevated nitrogen (N) deposition, predominantly as ammonium (NH ), causes significant nitrate (NO ) leaching from well-drained acid forest soils on hill slopes (HS), whereas significant retention of NO occurs in near-stream environments (groundwater discharge zones, GDZ). To aid our understanding of N transformations on the catchment level, we studied spatial and temporal variabilities of concentration and natural abundance (δ N and δ O) of nitrate (NO )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 63 publications
4
36
0
Order By: Relevance
“…The low DOC concentration in the groundwater discharge zone seems to contradict with our assumption (Figure f; Gundersen, ), but it may indicate a rapid decomposition of DOC in the valley bottom and the groundwater discharge zone. This is expected to drive reductive processes, as recently shown by the strong denitrification activity in the valley bottom and groundwater discharge zone, which is indicated by the sharp increase in natural abundance of 15 N and 18 O of NO 3 − (Yu et al, ).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The low DOC concentration in the groundwater discharge zone seems to contradict with our assumption (Figure f; Gundersen, ), but it may indicate a rapid decomposition of DOC in the valley bottom and the groundwater discharge zone. This is expected to drive reductive processes, as recently shown by the strong denitrification activity in the valley bottom and groundwater discharge zone, which is indicated by the sharp increase in natural abundance of 15 N and 18 O of NO 3 − (Yu et al, ).…”
Section: Discussionmentioning
confidence: 83%
“…An alternative explanation for the lower CH 4 emission in the valley bottom may be the inhibition of methanogenesis by other electron acceptors such as NO 3 − and SO 4 2− (Conrad, ; Le Mer & Roger, ; Veldkamp et al, ). Along the TSP catchment, the concentrations of NO 3 − and SO 4 2− in soil remain high in the valley bottom (NO 3 − ; Figures h and S3) until significant denitrification (Yu et al, ) and sulfate reduction (Yu, Si, et al, ) take place in the groundwater discharge zone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These scenarios differ fundamentally from observations in South China, where large amounts of NO 3 − are produced in well‐drained top soils on hillslopes and removed in groundwater discharge zones (Larssen et al, ). In a previous study in SW China, we observed a robust multi‐year 15 N and 18 O pattern in nitrate (NO 3 − ) along a hydrological flow path in a headwater catchment, suggesting that large amounts of NO 3 − are produced by nitrification on hillslopes and transported by interflow over argic horizons of common Acrisols to wet soils in groundwater discharge zones, where they are denitrified (Yu, Zhu, Mulder, & Dörsch, ). Similar geomorphological and soil‐related patterns of N turnover, transport and removal have been recently reported in temperate and subtropical systems (Anderson, Groffman, & Walter, ; Griffiths et al, ).…”
Section: Introductionmentioning
confidence: 86%
“…Most published δ 15 N−NO 3 − data are from heavily impacted systems in Europe, the eastern USA, northern Europe, and China (e.g., Hastings et al 2003;Elliott et al 2007Elliott et al , 2009Zhang et al 2008;Fang et al 2011;Koszelnik and Gruca-Rokosz 2013;Korth et al 2014;Yang et al 2014;Guerrieri et al 2015;Yu et al 2016). In general, fewer studies with NH 4 + isotopes in atmospheric deposition are available (e.g., Garten 1992;Zhang et al 2008).…”
Section: Introductionmentioning
confidence: 99%